A retrospective research on non-suicidal self-injurious behaviors among young patients diagnosed with mood disorders - Zheng, Yage; Xiao, Ling; Wang, Huiling; Chen, Zhenhua; Wang, Gaohua (Frontiers in Psychiatry, 2022)
Background: Non-suicidal self-injury (NSSI) is an emerging public concern in both clinical and non-clinical settings, especially in the background of COVID-19 pandemic. Nevertheless, knowledge of NSSI on a certain disease entity in the later stage of the pandemic was scarce. Objective: This study was conducted for the purpose of exploring current occurrence and characteristics of NSSI in patients diagnosed with Mood Disorders (MD) as well as its correlated factors in the later stage of pandemic. Method: Three hundred and forty nine eligible subjects (M ± SD, 21.54 ± 7.62) admitted to a mental health center in Wuhan during November 11, 2021 to January 31, 2022 were included into our study. An umbrella questionnaire comprised of demographics, COVID-19 related factors, Yale-Brown Obsessive and Compulsive Scale (Y-BOCS), Pittsburgh Sleep Quality Index-Revised (PSQI-R), Mobile Phone Addiction Index (MPAI), Ottawa Self-injury Inventory (OSI) was extended to each subject via shared QR code. Results: Of 349 MD patients included, 151 (43.27%) reported NSSI in recent 1 month, among whom hand, lower arm/wrist, scalp were the most hurt body parts, cutting, hitting, headbanging were the most adopted methods. "Own idea" was the most common origin of NSSI. In the logistic regression model, age bracket, family monthly income, occupation, level of OCD symptoms, sleep duration, withdrawal reaction to mobile phone, habits of using mobile phone were independently associated with NSSI. Conclusion: It was revealed by our study that NSSI was quite prevalent amongst patients with MD, especially among those students, adolescent, comorbid with OCD symptoms, inadequate sleeping hours, suffering from withdrawal reaction to mobile phone. Further research on NSSI in various psychiatric disorders and even in non-clinical settings such as community population was in urgent need, since NSSI in China was not rare.